2022
DOI: 10.1111/1462-2920.16043
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural characterization of the cyanophage‐encoded phosphate‐binding protein: implications for enhanced phosphate uptake of infected cyanobacteria

Abstract: To acquire phosphorus, cyanobacteria use the typical bacterial ABC-type phosphate transporter, which is composed of a periplasmic high-affinity phosphatebinding protein PstS and a channel formed by two transmembrane proteins PstC and PstA. A putative pstS gene was identified in the genomes of cyanophages that infect the unicellular marine cyanobacteria Prochlorococcus and Synechococcus. However, it has not been determined whether the cyanophage PstS protein is functional during infection to enhance the phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Thus, it is likely that these PstS variants facilitate specific interaction with the cognate PstABC membrane bound components of the transport system of their preferred host (see also Zhao et al. [ 45 ]). In the six cases where pstS has not been acquired from the host genus, it is not clear what the host ranges of these phages are, and therefore, the interaction of these “incorrect” PstS types with their host’s PstABC requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that these PstS variants facilitate specific interaction with the cognate PstABC membrane bound components of the transport system of their preferred host (see also Zhao et al. [ 45 ]). In the six cases where pstS has not been acquired from the host genus, it is not clear what the host ranges of these phages are, and therefore, the interaction of these “incorrect” PstS types with their host’s PstABC requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…5a). To date, only one provirus genome encoding PhnCDE was detected 73 , and the periplasmic high-affinity phosphate-binding gene pstS was the most commonly reported AMG related to phosphorus transport 74,75 . The viral phoR, phoB and phnC were expressed at varying levels, with the highest reaching up to 4.8…”
Section: Cold Seep Viruses Regulate Microbial Phosphorus Cycling Via ...mentioning
confidence: 99%
“…To acquire phosphorus, cyanobacteria typically use an ABC-type phosphate transporter, consisting of a high affinity phosphate-binding protein (pstS) and two transmembrane proteins (pstC and pstA; Kamennaya et al, 2020). Studies have shown that the pstS gene in cyanophages can be effectively expressed during host infection and improve the phosphate uptake rate of the host after infection (Zhao et al, 2022), which may contribute to adaptation of the cyanophage to the oligotrophic environment. Coincide with our observation, pstS has been suggested to be one of the genes contributing to the difference in AMG content between coastal and open ocean phage isolates (Fuchsman et al, 2023).…”
Section: Large Numbers Of Amgs To Enhance the Fitness Of Nanhaivirus ...mentioning
confidence: 99%